The impact of decision support systems in achieving organizational Ambidexterity An exploratory study in a sample of banks registered in the Iraq Stock Exchange - Anwar Hadi Aldabbagh (Scholars Digest Publishing, 2023)
This study basically investigates the extent to which operating departments in the Iraqi private bank (IPB) adapt to decision support systems (DSS) affect the achievement of organizational ingenuity (OI). The researcher gathered the data from 130 participants working in IPB at different administrative and department levels. They answered a questionnaire on DSS and OI. Results showed that adopting DSS significantly correlates with in achieving organizational ingenuity in IPB. Results also reported that adopting DSS has a significant impact on the achievement of organizational ingenuity. The study recommends the adoption of digital mechanisms to cooperate with associations and companies responsible for providing jobs and encouraging civil society organizations of developing mechanisms and programs for exploring and investing environmental opportunities in accordance with the rapid changes.
Keywords: ecision support systems (DSS), Iraqi private bank (IPB) organizational ingenuity (OI)